Human herpes virus antibody levels in helminth treated and placebo controlled multiple sclerosis patients - Maple, P.A.C. (2018)
In the UK, multiple sclerosis (MS) is the leading cause of non-traumatic disability in young adults. MS most commonly presents in a relapsing-remitting form (RRMS); however, over time, a progressive, neurodegenerative pathology dominates, and the disease enters a secondary progressive phase. Approximately, 10-15% of MS cases are primary progressive, some with superimposed relapses. During RRMS an underlying autoimmune pathology presides which leads to nerve damage through inflammatory processes. Therapeutic modulation of these inflammatory processes is beneficial in reducing relapses and increasing the periods between them. A key approach is to induce a switch in immune system reactivity from a proinflammatory (T helper1) to a less inflammatory (T helper2) profile. Immune system regulation is faulty in MS and reconstitution of regulatory T and B cell activity is a goal of effective intervention strategies. There is evidence that Intestinal parasite (helminth) infection is protective for MS as it induces a T helper2 profile and promotes regulatory cell activity. Deliberate, controlled helminth infection may be a useful therapeutic intervention.